Trace Element Concentration in the Blood and Aqueous Humor of Subjects with Eye Cataract - Forte, Giovanni; Battagliola, Edoardo Trovato; Malvasi, Mariaelena; Ruberti, Niccolò; Daniele, Pierluigi; Mantovani, Alberto; Bocca, Beatrice; Pacella, Elena (Biological trace element research, 2025)
Cataract, characterized by the opacification of the lens, is the leading cause of reversible blindness and visual impairment globally. The study aims to investigate the role of trace elements such as Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Se, and Zn in the development and severity of cataract. Elements were quantified by inductively coupled plasma mass spectrometry in blood and aqueous humor of 32 cataract cases and 27 controls living in the Latium region, Italy. The association between element concentration in blood and aqueous humor and cataract severity, gender, and age of subjects were also assessed. Results showed Cr levels significantly elevated in both blood and aqueous humor of cataract cases, with concentrations that increased with cataract severity. In addition, blood Pb levels were significantly higher in older cases and positively correlated with the age of cataract cases, while blood Co and Cu levels negatively correlated with cataract severity, suggesting changes in the levels of these elements. In conclusion, this study provides evidence of the involvement of specific elements in cataract development and severity, and the findings highlighted important avenues for future research. Understanding the biological mechanism underlying element-induced cataract may contribute to preventing cataractogenesis and providing targeted interventions.